Is Non-Restorative Cavity Treatment a Practical Choice in Primary Teeth? - Shetty, Amarshree A.; Acharya, Aditi; R., Manju (Journal of Health and Allied Sciences NU, 2022)
For years, “extension for prevention” was considered as the standard protocol for the restoration of caries. With advances in the field of cariology regarding the biofilm and improvement in materials, this perspective is being challenged. This is being challenged by more biological and less-invasive approaches, where the emphasis is on biofilm alteration to arrest carious lesions. This minimally invasive intervention is based on the concept that biofilm overlying the carious lesion is a driving force for the carious process and not the bacteria present in the infected dentin. Hence, daily removal or disruption of this biofilm will slow down the carious process or bring it to halt.One such approach is non-restorative cavity treatment, where no caries is removed but lesions are made self-cleansable that allows it to be brushed by the parent or the child. This wholesome approach targets the disease at a causal level.This review of literature describes the various advantages and limitations of this technique and the practicability of its use in pediatric patients during the pandemic COVID-19.
Keywords: biological caries management; NRCC; NRCT